ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT. BIO NUSANTARA TEKNOLOGI Jl. Lintas Utara Km. 19 Bengkulu Tengah - Merta Kusuma; Tm Said (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Merta Kusuma, Tm. Said:The purpose of this research is to know the influence of motivation, work environment, selection, and training toward employee’s performance in PT BIO Nusantara Teknologi. Population of this research was 550 permanent employees in PT BIO Nusantara Teknologi. Sampling techniques that used in this research were Nonprobability and Insidental sampling. To determined the sample used Solvin formula, so there was 84 people as samples. Data collection techniques were observation questionnaire, and interview. Data analysis techniques used by researcher were qualitative and quantitative analysis which consists of a multiple regression model and coefficient of determination. The result of this research used regression test Y= 6.003 + 0.230 X1 + 0.134 X2 + 0.188 X3 + 0.232 X4. While the result of determination R =  0.472 and R2 = 0223. T test significant level < 0,05 so, there was significant influence, if significant level > 0,05 so, there was not significant influence, the result of each t sig was 0,021 for motivation variable, 0,034 for work environment variable, 0,045 for selection, and 0,049 for training variable. The four variables were < 0,05 so there was significant influence. Next, F test, if F sig < 0,05 and (Fanova > F table) so, Ho was rejected ad H1 was accepted, the result of F sig=(0,000) < 0,05 and (5,673>2,337)so, the regression model can be used to predict employee’s performance variable or it can be said that the motivation variable (X1), work environment(X2), selection(X3), and training(X4) were influenced employee’s performance(Y) together in PT BIO Nusantara Teknologi.Key Words: Motivation, Work Environment, Selection, Training and Employee’s Performance.